MODERN ASPECTS OF INFUSION AND TRANSFUSION THERAPY IN PREGNANT WOMEN WITH PREECLAMPSIA - AKHMEDOV, Farhod (Journal of Experimental Studies, 2023)
Preeclampsia remains the massive problem modern obstetrics. Is of great importance in problems preeclampsia aspects therapy. The Purpose of our study was: study of the condition of the system heamostaz and heamoreologi, estimation of the influence upon them infusion therapy beside pregnant with preeclampsia. On base of the work prescribed results prospectus of the examination 95 pregnant with preeclampsia. Depending on program conducted infusion therapy. Pregnant with preeclampsia were divided into 2 groups. The Main group has formed 58 pregnant, got preparations GEK (rеfortan 6%, rеfortan -plus 10%, stabizol 6%). Researched the factors vascular, trombositar and coagulation heamostaz. The Track record of the factors vascular- trombositar heamostaz under influence infusion a therapy increase amount. trombosit was characterized by with using preparation GEK, observable was a shift in factor heamorealogi. The Results of the study coagulation heamostaz pointed to presence trombogen to situations. be accompanied expressed change the system heamostaz and reologik characteristic shelters. Transfuse decstran rendered the significant influence upon vascular, trombositar heamostaz and minimum on coagulation. The Got results afford ground recommend the solutions GEK to broad using under preeclampsia and eclampsia also beside pregnant with chronic arterial hypertension.